A Comprehensive Review of Historical and Ethnobotanical Aspects, Chemical Constituents and Biological Activities of Euphorbia umbellata (Pax) Bruynsq - Siani, Antonio Carlos; Abreu, Lívia (Pharmacognosy Reviews)
Euphorbia umbellata (Pax) Bruyns (Synadenium grantii Hook.f.) is an African shrubby tree that has a long use in traditional human and veterinary medicine. Nowadays in Brazil, its latex has been extensively used to treat arthritis and several types of cancer, among other health disorders. This study comprehensively reviewed data reported on history and ethnopharmacological aspects of E. umbellata, as well its chemistry and preclinical pharmacology. The Web of Science, SciFinder, Google Scholar and the Prelude Medicinal Plants database were prospected by using the three precedent botanic synonymous for the species. The resulting assembly was complemented by searching available online monographs, and physical and online books on the theme. The compiled information was organized according to each specific survey. Thirty-three distinct popular uses and approximately forty recipes were found for the latex and leaves. Oral and topical administrations of latex or leaves were predominant in human cases. Veterinary uses mostly targeted antiparasitic and anti-inflammatory therapy, and topical application of latex stood out. Prospection of the experimental studies led to twenty-four entries for biological activities in vitro, mainly related to anticancer investigations. Thirty-five compounds comprising triterpenes, diterpenes and phenolics, besides typical proteases, have been characterized in the species. Traditional usage of E. umbellata may be correlated with results on the cytotoxicity, antiviral, and anti-ulcer ability of extracts from diverse parts of the plant. To date, the most significant experimental progress has been related to E. umbellata terpenoidal metabolites.
Keywords: Ethnomedicine; Euphorbia umbellata; Phorbol esters; Synadenium grantii; Synadenium umbellatum; Triterpenes